Alcohol exposure impairs trophoblast survival and alters subtype-specific gene expression in vitro. (October 2016) - Kalisch-Smith, J.I.; Outhwaite, J.E.; Simmons, D.G.; Pantaleon, M.; Moritz, K.M.
Abstract: Maternal alcohol consumption is common prior to pregnancy recognition and in the rat results in altered placental development and fetal growth restriction. To assess the effect of ethanol (EtOH) exposure on the differentiation of trophoblast stem (TS) cells, mouse TS lines were differentiated in vitro for 6 days in 0%, 0.2% or 1% EtOH. This reduced both trophoblast survival and expression of labyrinth and junctional zone trophoblast subtype-specific genes. This suggests that fetal growth restriction and altered placental development associated with maternal alcohol consumption in the periconceptional period could be mediated in part by direct effects on trophoblast development. Highlights: Trophoblast cell survival in vitro was inhibited by ethanol. Ethanol reduced gene expression of trophoblast subtype-specific markers. Results suggest ethanol exposure can directly alter the viability of mature trophoblasts.